An ethnography on boxing: The role of the coach - Coates, S. (1999)
The reactions towards the sport of boxing are either love or hate: views are rarely indifferent. To date it has been the negative side of boxing which has received much of the attention as opposed to studies which approach the sport from the boxer's point of view. This ethnographic study was investigating boxing from a lesser known and less spectacular reality; the one contained within the gym where the endless preparation, training and coaching takes place. Thus, the aim of this paper is to report some of the findings of the study, focussing on the various roles of a boxing coach in an inner city gym. Conclusion: The theories which surround boxing commonly refer to social structural features in order to account for its nature. With regard to those young men who take part in the sport, they are identified as coming from poor inner city areas with a background of street fighting and violence. However, what these theories fail to account for are the points of view of the boxers and how they make sense of what it means to be a boxer, and in particular the influence of the coach as a significant other. Boxing offers an alternative lifestyle to the structural opportunities within their environment. The gym offers structure and support: the support via other gym members, a strong one-to-one relationship with the coach and the structure of employment which offers a route to increased social status. The coach plays an important role in the self-development of a boxer and in building a trusting relationship. These findings concur with Wacquant (1995) who reports "Trainers likewise construe their work partly as a civic venture that benefits not only the boxer and his family but the broader society as well" (p.518). The boxers' interviewed in this study did have other options and educational qualifications but had chosen to box. The gym members enjoyed boxing for what it provided them i.e., the social atmosphere, the adrenalin high, recognition, financial reward and status. Boxing is a form of employment and encompasses many different areas and a number of different players, including crucially the coach; a relationship worthy of further research.